2022
DOI: 10.7759/cureus.28696
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Residency Point-of-Care Ultrasound Training Needs Assessment and Educational Intervention

Abstract: BackgroundPrior studies showed that point-of-care ultrasound (POCUS) training is not commonly offered in pediatric residency. We assessed the need for a pediatric POCUS curriculum by evaluating pediatric trainees' attitudes toward the use of POCUS and identifying barriers to training. We also aimed to evaluate the impact of a POCUS educational intervention on self-efficacy and behavior. MethodsWe conducted a cross-sectional survey of pediatric residents in a single large freestanding children's hospital distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The current study suggests that partnerships between pediatrics and emergency medicine may be an effective strategy for teaching POCUS basics to pediatric residents because a lack of qualified educators within pediatrics is reported as a barrier to providing this education [ 7 - 9 ]. While other programs have effectively utilized PEM program faculty to teach POCUS, many pediatric residency programs do not have access to a PEM training program [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study suggests that partnerships between pediatrics and emergency medicine may be an effective strategy for teaching POCUS basics to pediatric residents because a lack of qualified educators within pediatrics is reported as a barrier to providing this education [ 7 - 9 ]. While other programs have effectively utilized PEM program faculty to teach POCUS, many pediatric residency programs do not have access to a PEM training program [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…When surveyed, most pediatric residents believed their residency programs should teach them how to use POCUS [7]. However, many pediatric residencies do not currently teach POCUS, with reported barriers including a lack of an established curriculum and a lack of qualified educators [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of or inadequate diagnostic imaging equipment is reported as a major barrier for US implementation also in low- and middle-income countries, as underlined in a recent sistematic review [ 11 ]. Definitely, the availability of US equipment and machines throughout various clinical settings should be enhanced, also favoring the use of portable and handheld devices with lower cost but good resolution [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a demonstrated demand for POCUS education to be included in pediatric residencies both from the perspective of program leadership as well as from pediatric trainees. One survey of pediatric residents at a free-standing children’s hospital found that 96% felt that POCUS was an important skill in pediatrics 18 . In a separate survey, pediatrics residents overwhelmingly felt that POCUS training should be required during residency, yet only 15% of respondents had received such training 19 .…”
Section: Introductionmentioning
confidence: 99%